Advantages and disadvantages of the enacted law of Ukraine On amendments to the Law of Ukraine - Kulyk, T.; Kulyk, М. (Ways to Improve Construction Efficiency, 2019)
Three methods of normalization in construction are analyzed: management, target and parametric. Recently, a regulatory method of normalization in construction has been used in Ukraine, which consists in a more elemental description of a construction object, in accordance with which solutions, structures, materials, performance, etc. are offered. The application of the regulatory method of regulation does not provide an alternative, does not clarify the objectives of the regulations, do not formulate, as a rule, functional requirements for the function that the object of construction should perform. The parametric rationing method is based on a hierarchy of goals and objectives and is more progressive. It involves setting the parameters that determine the safety, functionality, and quality of the entity. The parameters are goals, functional requirements and criteria that the entity should meet. The target method is transient and includes elements of the control and parametric methods. This method was developed as an evolutionary transition in order to prevent unwanted consequences in the abrupt transition from the regulatory method to the parametric The advantages and disadvantages of the parametric method of rationing, which becomes a priority with the enactment of this law, are analyzed. This makes it possible to develop better building standards that do not contain unreasonable design requirements and will promote the use of innovative and advanced technologies and solutions. The procedure of promulgation of building norms is being improved. The texts of state building codes included in the central building code fund and industry building codes included in sectoral building code funds shall be published on the official websites of the relevant constituent entities. Access to such texts will be free of charge. It is established that the adoption of the law provides an opportunity to improve the quality of building codes and reduce the number of unreasonable mandatory requirements, which will contribute to the introduction of innovative and progressive technologies, enhance the investment attractiveness of the construction market and further development of the construction industry.